Comorbid Description and Neutrophil Lymphocyte Ratio in COVID-19 Patients (Suspect and Confirmed Patients) - Widada , Subrata Tri; Martsiningsih, Marta Atik; Supriyanta, Bambang; Sistiyono; Suyana; Nuryani, Siti; Setiawan, Budi; Sulistyowati, Dwi; Muji Rahayu (JURNAL INFO KESEHATAN, 2022)
Neutrophil Lymphocyte Ratio (NLR) is a laboratory available as a marker used for the evaluation of systemic inflammation, NLR is a significant predictor and is a critical prognosis for COVID-19 infection and can serve as a useful factor to reflect the intensity of the imbalance of inflammation and immune response in COVID-19 patients. This study aims to determine the difference in NLR values in negative and confirmed COVID-19 patients and description for comorbid for both. This study is an analytic observational study with a cross-sectional design. The study sample was 423 suspected COVID-19 patients at hospitals in Cilacap district for the period in March – October 2020. The data obtained were analyzed descriptively and using the fisher-exact test. In these results from suspected patients with negative COVID-19, lung illness were present 31.8%, viral infections 22.9%, other respiratory disorders 6.1%, diabetes mellitus 4.7%, and anemia 4.7%. Whereas suspected patients with confirmed COVID-19 were, without comorbid diseases (40.2%), lung disease (12.4%), diabetes mellitus (7.7%), hypertension (6.2%), and other respiratory illnesses (5.2%). The mean of NLR in confirmed patients is 3.57 but not any difference between negative and confirmed patients COVID-19, but there’s any a relationship between NLR and ARDS conditions.